Analysing unsuccesful experiments and instruments with the replication method - Heering, Peter (ENDOXA, 2005)
The aim of this paper is to discuss instruments and experiments from the history of physics that were rejected in the historical situation. As a consequence, only very few of these devices were produced —and virtually none of them did survive. Thus, in order to develop an understanding of the experimental practice connected with these devices the replication method is applied. In short, this method— which will be discussed on a general level in the first part of the paper —is based on self-reflexive interaction with reconstructed apparatus and the contextualisation of the experiences made in the laboratory. The example of experiments published by Jean Paul Marat in the 1780ies shall illustrate the usefiílness of this method in order to develop an understanding of experiments that were rejected in the historical situation.